HEAVY METALS CHROM AND CUPRUM CONTENT IN THE FEATHERBACK FISH (Notopterus notopterusPallas, 1796) FROM THE DOWNSTREAM OF SAIL RIVER, PEKANBARU - Nostalgia, Dairiyanti; Harahap, Sampe; Budijono, Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractFeatherback fish (Notopterus notopterus) is a type of freshwater fish that inhabit the Sail River. Pollutant that may contain heavy metals may contaminate the fish living in that area. Information on the content of Cr and Cu in the fish living in that area is rare. To understand the Cr and Cu content in the liver, kidney and bone of the fish, a research had been conducted on December 2017 to January 2018. The fish captured was categorized into 3 groups, namely small (12.7-20.2 cm), medium (20.3-27.7 cm) and large (> 27.8 cm) sizes. Results shown that there were 35 fishes caught. The Cr and Cu content in the liver as well as the kidney increased as the fish growing. The Cr content was39.455 to 95.62 mg/kg in the liver and 34.025 to 65.29 mg/kg in the kidney, while the Cu content was 6.635 to 14.265 mg/kg in the kidney and 5.085 to 7 mg/kg in the liver. In contrast, the Cr and Cu content in the bone decreased as the fish growing, there was 76.79 to 20.31 mg/kg of Cr and 15.825 to 6.59 mg/kg of Cu content in the bone. Keywords : freshwater fish, polluted river, heavy metal content, contaminated fish